Effects of antenatal education on maternal anxiety and depression in pregnancy and postpartum period in Italy: modest and transient symptom reductions - Camoni, Laura; Mirabella, Fiorino; Gigantesco, Antonella; Calamandrei, Gemma; Stefana, Alberto; Aceti, Franca; Adulti, Ilaria; Bagolan, Pietro; Barbano, Gina; Bellomo, Antonello; Cattaneo, Marina; Cengia, Elda; et al. (Frontiers in Psychology, 2026)
IntroductionAntenatal classes have increasingly been integrated into healthcare practices in most middle- and high-income countries over recent decades. The aim of the present study was to compare levels of anxiety and depressive symptoms during pregnancy and the postpartum period among (a) women who attended antenatal classes and (b) women who did not participate in antenatal education.MethodsWe analyzed 9,689 perinatal respondents recruited in eight Italian regions between October 2021 and December 2024. Each participant was assessed once, during their pregnancy (n = 4,169) or their postpartum period (n = 5,520), and completed the General Anxiety Disorder-7 (GAD-7) and Edinburgh Postnatal Depression Scale (EPDS) scales. The cut-off scores to identify women at risk for depression and anxiety were ≥12 and ≥10 for EPDS and GAD-7, respectively. Propensity scores based on socio-demographic and clinical covariates were estimated with multiple imputations and inverse-probability-of-treatment weighting (IPTW).ResultsAttendance was frequent (47%). Crude models showed that, during pregnancy, class participants had lower mean scores (ΔGAD = −0.8; ΔEPDS = −1.0) and markedly lower odds of screening positive (OR = 0.58 for anxiety; 0.45 for depression). After IPTW adjustment these associations weakened and became non-significant (pregnancy OR = 0.86, 95% CI 0.54–1.35 for anxiety; 0.64, 0.38–1.10 for depression); all post-partum IPTW estimates were similarly null (ORs 0.96 and 0.83, CIs span 1). E-values (1.9–2.5) indicated that moderate unmeasured confounding could erase the residual pregnancy effects.ConclusionsOur results suggest antenatal education classes are modestly effective in reducing anxiety and depressive symptoms during pregnancy. However, these modest prenatal improvements attenuate after adjustment and do not persist into the postpartum period. This indicates a need for standardized, evidence-based antenatal education that is integrated into broader psychosocial support frameworks.